Tonic status epilepticus in a centenarian woman - Fernández‐Torre, José L.; Riancho, Javier; Martín‐García, María; Martínez‐de las Cuevas, Gonzalo; Bosque‐Varela, Pilar (Epileptic disorders, 2019)
ABSTRACT Generalized tonic status epilepticus (TSE) is a rare epileptic condition. It occurs usually in the context of symptomatic generalized epilepsy, in particular, in subjects with a diagnosis of Lennox‐Gastaut syndrome, atypical forms of idiopathic (genetic) generalized epilepsy, or as a paradoxical effect during treatment with diverse antiepileptic drugs. Herein, we describe the case of an elderly woman on chronic treatment with psychotropic drugs who developed an episode of generalized TSE. Motor manifestations were subtle and difficult to recognize as seizures, and a detailed video‐EEG importantly contributed to accurate and prompt diagnosis. TSE was initially refractory to conventional anti‐seizure drug therapy including levetiracetam and valproate but was finally controlled with lacosamide. Our case indicates a potential therapeutic effect of lacosamide on TSE in the elderly after treatment failure with first‐line anti‐seizure drugs. [Published with video sequence on www.epilepticdisorders.com]